THE EXPERIMENTAL VERIFICATION OF PEDAGOGICAL CONDITIONS OF FUTURE TOURISM BACHELORS PREPARATION FOR PROFESSIONAL INTERACTION BY means OF PROJECT TECHNOLOGIES - Olha A. Derbak; Kateryna Yu. Pecherna; Tetiana I. Yakovleva (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2021)
The article considers the experimental verification of pedagogical conditions for the preparation of future tourism bachelors for professional interaction by means of project technologies. The concept of the study was substantiated, which was that the effectiveness of training future tourism bachelors for professional interaction by means of project technologies will be implemented subject to the application of certain pedagogical conditions, namely: a combination of different types of projects in the preparation of future bachelors in tourism; creating an atmosphere of partnership between lecturers and students in the educational environment of higher education institutions on the basis of a project approach; organization of independent work of future tourism bachelors through interdisciplinary project activities. The study was conducted in three stages. The statement stage gave us the opportunity to analyze the state of the problem research; to form a hypothesis, purpose and tasks of the experiment; to analyze and elaborate the educational-professional program of preparation of future bachelors in tourism in the specialty 242 Tourism, working programs of academic disciplines; to determine the level of readiness for professional interaction of future tourism bachelors; theoretically substantiate the pedagogical conditions for the preparation of future bachelors in tourism for professional interaction by means of project technologies; to establish the quantitative and qualitative composition of the control participants and experimental groups, to analyze the homogeneity of the studied groups; to determine diagnostic tools to identify the level of readiness of future tourism bachelors for professional interaction and to obtain initial data on the actual practice of forming this readiness. A description of the formative stage of the experiment, which provided for experimental testing and implementation in the educational process of higher education institutions of pedagogical conditions for preparing future tourism bachelors for professional interaction by means of project technologies, analysis of the results of control groups. The result of the control phase of our study was a final check of the levels of future tourism bachelors readiness for professional interaction, which showed a change in the distribution of higher education in accordance with all components of readiness. It is concluded that the influence of the realized pedagogical conditions of future tourism bachelors preparation for professional interaction by means of project technologies is a significant factor and a significant element of increasing the level of future tourism bachelors readiness for professional interaction of the experimental group.